Rethinking mental healthcare: operationalising intersectionality through a community-driven social clinic model - Kapilashrami, Anuj; Kokkinidis, George; Checchi, Marco (My University, 2025)
Here we examine the critical need for rethinking mental healthcare through a social clinic model, informed by intersectional equity perspective. Drawing on insights from the INtersectional Network Of community and stakeholder Voices, And research to Tackle (in)Equities (INNOVATE) project, we highlight significant gaps in current mental health services, including fragmentation, stigmatisation, and lack of person-centred care. Intersectionality recognises intersecting disadvantages that shape differential mental healthcare access and outcomes. By applying an intersectionality lens, we reveal how overlapping forms of disadvantage arising from social positions such as race and ethnicity, gender, geography, and immigration status interact with social drivers like socio-economic deprivation, legal status, and exclusion to create complex barriers to accessing care. For instance, young people in remote areas, asylum seekers with housing insecurity and experiencing disability, and those in socioeconomically deprived areas carry a disproportionate burden of poor mental health in Essex, UK. Social clinics, as autonomous, self-managed centres that combine medical care with social support and community participation, constitute a promising approach to reduce the gap. We argue for a community-led process of the integration of intersectionality into community engagement processes for establishing and implementing social clinics to build sustainable, inclusive, and responsive mental health services. We propose a five-step framework for operationalising this model, centred around co-design, collective action, and participatory governance, aiming to address power asymmetries and promote equity in mental health service delivery.